Novel computed tomography angiography‐based sizing methodology for WATCHMAN FLX device in left atrial appendage closure. (26th May 2022) - Dallan, Luis Augusto Palma; Arruda, Mauricio; Yoon, Sung‐Han; Rana, Mohammad Atif; Mogalapalli, Akhil; Carneiro, Herman A.; Reed, Joseph; Rashid, Imran; Rajagopalan, Sanjay; Filby, Steven J.
Abstract: Background: While there is recent data suggesting an advantage of computed tomography angiography (CTA) over transesophageal echocardiography (TEE) for preprocedural left atrial appendage closure (LAAC) planning, there is limited published experience for sizing strategies. Device sizing for LAAC may be challenging and noninvasive algorithms that improve this selection process are warranted. Objectives: We sought to evaluate the safety and the feasibility for the implementation of a novel CTA‐based sizing methodology for WATCHMAN™ FLX device in a series of patients undergoing LAAC using the TruPlan™ software package. Methods: A prospective analysis of 136 consecutive patients who underwent LAAC over a 12‐month period in a single, large academic hospital in the United States was conducted. CTA‐guided preprocedural planning and intracardiac echocardiography (ICE) was performed in all. Procedural success, adverse events, length of procedure, number of devices used, and length of stay were evaluated. Results: A total of 136 patients who underwent LAAC procedure with WATCHMAN™ FLX platform between October 1, 2020 until September 30, 2021 were included. The pre‐specified protocol using CTA and ICE was implemented in all patients (100%). Mean CHA2 DS2 VASc score was 4.4 ± 1.3 and the mean HAS‐BLED score was 3.9 ± 0.8. ICE‐guided 100% transseptal puncture success rate was 100% with 98.5% of overall procedural success rate. Preprocedural CTA sizing strategy accurately predicted the implanted size in 91.1% of patients. Ten patients (7.4%) required another sized device and 2 cases were aborted. At 45‐day follow‐up, only 1 patient (0.7%) had significant peri‐device leak (≥5 mm) on TEE. Conclusions: CTA‐based preprocedural sizing methodology for WATCHMAN™ FLX in LAAC was safe, feasible and associated with excellent procedural outcomes. Further studies are warranted to confirm if the features specific to TruPlan™ may reduce the number of deployment attempts, the number of devices utilized in the procedure, and the risk of complications.